A study on the process of teacher appraisal in selected full-time Islamic schools under Yayasan Islam Kelantan - Zaradah binti Zakaria (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 1998)
The study presented in this thesis is jusst part of the whole educational process pertaininbg to Islamic schools. It uncovers the practice of teacher appraisal in fifteen selected Islamic schools under Yayasan Islam Kelantan (YIK). The study used questionnaire and unstructed inerview for the purpose of getting enough data to be analysed. It was found in the study that teacher appraisal has not been taken as a systematic practice of the schools under Yayasan Islam Kelantan (YIK) untul the New Pension Scheme for teacher appraisal was introduced for years ago. Since then teacher appraisal has been conducted in a way suitable to both the teachers and the principals, with special attention given to appraisal interview rather than combining a few methods together. Classroom observation, which was thought to be the main focus in appraising teachers, has not been taken seriously due to certain reasons which will be mentioned later in the analsis. In order for the schools to proceed with a better system in appraising teachers, Yayasan Islam Kelantan (YIK) needs to come up with a suitable trainin for the appraisers regularly. Despite the shortcomings that they face in appraising teacheers, the principals and their assistants admitted that most of them are responsible and sincere in performing their jobs as teachers. What concerns them most is the blessings from Allah s.w.t.